2018
DOI: 10.3389/fgene.2018.00336
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence of Members of TRAF and DUB of Ubiquitin Proteasome System in the Regulation of Hypertrophic Cardiomyopathy

Abstract: The ubiquitin proteasome system (UPS) plays an imperative role in many critical cellular processes, frequently by mediating the selective degradation of misfolded and damaged proteins and also by playing a non-degradative role especially important as in many signaling pathways. Over the last three decades, accumulated evidence indicated that UPS proteins are primal modulators of cell cycle progression, DNA replication, and repair, transcription, immune responses, and apoptosis. Comparatively, latest studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 214 publications
0
14
0
Order By: Relevance
“…It interacts with itself and can form hetero- and homo-oligomeric structures. The MATH domain is shared with other ubiquitin ligases, called TRAFs, and is involved in facilitating protein–protein interactions [11]. The MATH domain is thus also known as Tumor-necrosis-factor (TNF) receptor-associated factor (TRAF)-C domain.…”
Section: Trim37 Organization Of the Gene Gene Expression Proteimentioning
confidence: 99%
“…It interacts with itself and can form hetero- and homo-oligomeric structures. The MATH domain is shared with other ubiquitin ligases, called TRAFs, and is involved in facilitating protein–protein interactions [11]. The MATH domain is thus also known as Tumor-necrosis-factor (TNF) receptor-associated factor (TRAF)-C domain.…”
Section: Trim37 Organization Of the Gene Gene Expression Proteimentioning
confidence: 99%
“…8 In addition, mounting evidence has demonstrated that many TRIMs, including TRIM8/21/24/32/45/67/72, play important roles in cardiac function and disease, for example by regulating cardiomyocyte differentiation and apoptosis, cardiac atrophy, ischemia-reperfusion injury, and dilated and hypertrophic cardiomyopathies. [8][9][10] TRIM10, another member of the TRIM family, is essential for the differentiation and survival of terminal erythroid cells. 11 However, functional roles and molecular mechanisms of TRIM10 during cardiac hypertrophy remain to be elucidated.…”
mentioning
confidence: 99%
“…In short, the findings suggest that UPS contributes to structural remodeling of the myocardium, ischemia-reperfusion injury and myocardial cell loss, important components of progressive heart failure. There is evidence for the non-degradative role as well, as the ubiquitination was shown to affect the important The functional insight into the genetics of cardiovascular disease: results from the post-GWAS study regulators of signaling pathways including those for the cell growth and apoptosis, DNA damage response, the innate immune response, endocytosis, and protein activity (reviewed partly in (Gupta et al, 2018)). Given that proteostasis is a dynamic multiple-step process involving complex molecular machinery, the deregulation at any stage could therefore be implicated in a wide variety of outcomes.…”
Section: Discussionmentioning
confidence: 99%